Political Theory and Immaterial Work in Marx – An Interview with André Tosel by Henrique Amorim - Amorim, Henrique (Pontifícia Universidade Católica de São Paulo, 2009)
In this interview conducted in June 2009 André Tosei discussions such questions as the relationship between labor value and the immaterial and cognitive transformations in production; the relationship between political economy and politics; the importance of the Grundrisse and their influence on contemporary social theory; the validity of the concept of social class in Gramsci; and the need to analytically break down the work of Marx.